Detection of Live Attenuated Measles Virus in the Respiratory Tract Following Subcutaneous Measles-Mumps-Rubella Vaccination - Watkins, Timothy A; Brockhurst, Jacqueline K; Germain, Gregory; Griffin, Diane E; Foxman, Ellen F (The Journal of infectious diseases, 2025)
The live attenuated measles vaccine is extremely effective in preventing measles and induces mucosal immunity in the respiratory tract; however, the mechanism is not known. We show that live attenuated measles virus (LAMV) RNA is frequently detected in the respiratory tract 7-21 days after subcutaneous measles-mumps-rubella (MMR) vaccination in healthy children (n = 5/20) and macaques (n = 6/8). Replicating LAMV was isolated from the lungs of 2 macaques, with no evidence of transmission to unvaccinated individuals. These observations suggest that LAMV in the respiratory tract may play a role in the development of robust mucosal immunity following MMR vaccination.